Crystal plasticity finite element–Marciniak-Kuczynski approach with surface roughening effect in predicting formability of ultra-thin ferritic stainless steel sheets. (1st February 2021) - Bong, Hyuk Jong; Lee, Jinwoo
Highlights: Forming limit diagrams of two ferritic stainless steel sheets are predicted. Crystal plasticity model is incorporated with M-K model. Surface roughening is further considered in predicting forming limit diagram. Role of surface roughening effect in ultra-thin sheet metal is highlighted. Deformation textures under various loading paths are predicted. Abstract: Forming Limit Diagrams (FLDs) of 0.1 and 1 mm thick ultra-thin ferritic stainless steel (FSS) sheets are predicted using a combination of the crystal plasticity finite element (CPFE) approach and the Marciniak-Kuczynski (M-K) model. In a scale of few microns, especially for thin materials, surface roughness significantly affects sheet formability; therefore, the M-K model is further modified to address the surface roughening effect. The CPFE combined M-K model with the surface roughening effect can reproduce experimental FLDs of two FSS sheets, unlike the method without considering the surface roughening effect. The results highlight the importance of surface roughening, particularly in thinner sheets, where the portion of surface roughness is an order higher than that in the thicker sheets. The evolution of the deformation texture under various loading paths is further investigated and discussed. The findings coincide with reports of previous studies. Graphical abstract: Image, graphical abstract